A generalized framework to consider positive and negative attributes in formal concept analysis - Rodríguez Jiménez, José Manuel; Cordero-Ortega, Pablo; Enciso-García-Oliveros, Manuel; Mora-Bonilla, Ángel (My University, 2014)
In Formal Concept Analysis the classical formal context is analized taking into account only the positive information, i.e. the presence of a property in an object. Nevertheless, the no presence of a property in an object also provides a signi cant knowledge which can only be partially considered with the classical approach. In this work we have modi ed the concept forming operators to allow the treatment of both, positive and negative attributes which come from respectively, the presence and absence of the properties. In this work we de ne the new operators and we prove that they are Galois connections. Finally, we have also studied the correspondence between the formal context in the new framework and the extended concept lattice, providing new interesting properties.
Keywords: Lógica; Formal Concept Analysis; Logic